Extreme temperatures amplify air pollution risks to childhood respiratory health in school environment in Jiangsu province, China - Yangyang Wu; Jie Yang; Jing Wei; Biran Cheng; Yiyi Wang; Chen Li; Peng Wang; Hong Sun; Lei Huang (Communications Earth & Environment)
Abstract Childhood respiratory diseases remain a major global health concern, with school-centered exposures to air pollution and extreme temperatures posing significant risks. We conducted a spatiotemporal stratified multi-city, school-based design to evaluate underexplored risk patterns of fine particulate matter with an aerodynamic diameter ≤1 µm, nitrate, sulfate, ammonium, chloride, black carbon, and temperature exposures including daily mean, extremes, and short-term variability. The analysis included 265,076 pneumonia and/or tracheitis cases among schoolchildren in Jiangsu Province, China. We observed significant urban–rural disparities and spatial clustering in air pollution and temperature variation. Cumulative exposure to all pollutants was positively associated with increased risk of illness-related absences, with stronger effects observed in urban schools and during low-temperature conditions overall. Boys showed higher initial sensitivity to air pollution, while girls exhibited greater vulnerability after 10–14 days. Notably, urban children were most affected by combined exposures to low temperature-high pollution, whereas rural children experienced greater combined risks under high-temperature conditions. In contrast, short-term temperature variability contributed minimally to the observed health effects. These findings support the development of early warning systems for composite exposures, informed by exposure–risk profiles, to enable timely school intervention and protect schoolchildren’s respiratory health.